Soil nutrient and cassava yield variations under continuous cultivation of three crop mixtures in southeastern Nigeria - Asadu, C.; Dixon, A. (2005)
A research farm at University of Nigeria, Nsukka, Nigeria, which was under cultivation for >25years before it was fallowed for 8 years, was cleared in 1998 and grown to three common crop mixtures for 4 years. The aim was to assess the performance of the cassava component in terms of root yield and harvest index under continuous cultivation relative to soil nutrient variations. The crop mixtures were cassava + pigeonpea, cassava + pigeonpea + maize, and cassava + pigeonpea + maize + yam. Incorporation of crop residues from each of the respective plots into the soils and the use of a legume (pigeonpea) served as means of restoring soil fertility. The experimental design was a randomized complete block design replicated thrice each year. Changes in eight selected soil fertil-ity indicators, namely, pH, total N, organic matter, available P, and exchangeable Ca, Mg, K, and Na were monitored for the period. An analysis of the nutrient contents of the soils under the crop mixtures indicated narrow variations over the four years, except in the cases of exchangeable cations where coefficients of variations of ≥25% were obtained. Comparatively, year-to-year variations were more substantial though not consistent. This is because in some years some nutrients decreased while others increased relative to the values obtained in the preceding year. Except in 1999 when cassava root yields from all the crop mixtures decreased substantially (>60%) relative to their 1998 respective values, the trends in other years were not consistent in all the crop mixtures. The mean yields obtained were generally below the expected mean yield for the same cassava variety in the area. The study also showed that all the soil parameters selected contributed to the variations in cassava yields, though they were not consistent in each year and in each crop mixture. However, regression analysis between the relative changes in soil nutrients and cassava yield variations showed significant contributions of total N (P= 0.05), exchangeable Ca (P= 0.01), and Mg (P= 0.001). Thus, adequate management of these soil factors is required to enhance the performance of cassava in the crop mixtures.